2003
DOI: 10.1523/jneurosci.23-32-10419.2003
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Anxiety, Altered Place Learning, and Increased CA1 Basal Excitatory Synaptic Transmission in Mice with Conditional Ablation of the Neural Cell Adhesion Molecule L1

Abstract: L1, a neural cell adhesion molecule of the immunoglobulin superfamily, is involved in neuronal migration and differentiation and axon outgrowth and guidance. Mutations in the human and mouse L1 gene result in similarly severe neurological abnormalities. To dissociate the functional roles of L1 in the adult brain from developmental abnormalities, we have generated a mutant in which the L1 gene is inactivated by cre-recombinase under the control of the calcium/calmodulin-dependent kinase II promoter. This mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 55 publications
1
69
0
Order By: Relevance
“…In fact, NCAM180 associates with NR2A-containing NMDA receptors in the central region of the postsynaptic membrane in hippocampus; this distribution changes following induction of long-term potentiation in vivo in adult rodents (Fux et al, 2003) where NCAMs help mediate synaptic plasticity (Bukalo et al, 2004). Similar to NCAMs, members of the L1 family are important both in synaptogenesis (Faivre-Sarrailh et al, 1999;Suh et al, 2004) and for synaptic plasticity in adult brain (Law et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, NCAM180 associates with NR2A-containing NMDA receptors in the central region of the postsynaptic membrane in hippocampus; this distribution changes following induction of long-term potentiation in vivo in adult rodents (Fux et al, 2003) where NCAMs help mediate synaptic plasticity (Bukalo et al, 2004). Similar to NCAMs, members of the L1 family are important both in synaptogenesis (Faivre-Sarrailh et al, 1999;Suh et al, 2004) and for synaptic plasticity in adult brain (Law et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The tyrosine kinase receptor Tie2 is expressed in early precursors of hematopoietic and ECs ( 7 ). Hence, transgenic mice expressing Cre recombinase under the control of the Tie2 gene promoter ( 8 ) were intercrossed with L1 f loxed mice carrying two f loxed alleles of the L1cam gene ( 9 ). The genotype of the mice was determined by PCR on genomic DNA ( Fig.…”
Section: Generation Of Conditional L1 Knockout Mice and Characterizatmentioning
confidence: 99%
“…Among the recognition molecules that mediate these functions is L1, a homophilically and heterophilically binding member of the Ig superfamily that is expressed by neurons but not by astrocytes and oligodendrocytes in the CNS and by neurons and Schwann cells in the peripheral nervous system (Lindner et al, 1983;Rathjen and Schachner, 1984;Moos et al, 1988;Appel et al, 1993;Kamiguchi and Yoshihara, 2001). L1 promotes neuronal survival, neurite outgrowth (Lemmon et al, 1989;Appel et al, 1993;Chen et al, 1999;Kleene et al, 2001;Dong et al, 2003), and synaptic plasticity, as shown by modification of synaptic efficacy both in vitro and in vivo as well as in learning and memory as seen in L1-deficient mice and humans (Luthi et al, 1996;Fransen et al, 1998a,b;Tiunova et al, 1998;Wolfer et al, 1998;Demyanenko et al, 1999;Pradel et al, 2000;Law et al, 2003;Saghatelyan et al, 2004;Venero et al, 2004). Furthermore, L1 is involved in myelination in the central and peripheral nervous systems (Seilheimer et al, 1989;Wood et al, 1990;Haney et al, 1999;Barbin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%